1963
DOI: 10.1111/j.2517-6161.1963.tb00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Distributions for Multivariate Normal Parameters

Abstract: A class of Bayes posterior distributions is obtained for the parameters of the multivariate normal distribution. These are compared with their fiducial and confidence counterparts..collectively Bayesian, that the hope of finding a "nice" criterion that invariably leads to Bayesian confidence limits when they exist cannot be realized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
3

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 7 publications
1
63
0
3
Order By: Relevance
“…Note that for k = 1, it is equal to the independence-Jeffreys prior. Furthermore, Geisser and Cornfield [13] used that prior distribution over the mean vector and the covariance matrix of a multivariate normal distribution and showed that it yields a posterior distribution of the mean vector which reduces to the Fisher-Cornish fiducial density.…”
Section: General Casementioning
confidence: 99%
“…Note that for k = 1, it is equal to the independence-Jeffreys prior. Furthermore, Geisser and Cornfield [13] used that prior distribution over the mean vector and the covariance matrix of a multivariate normal distribution and showed that it yields a posterior distribution of the mean vector which reduces to the Fisher-Cornish fiducial density.…”
Section: General Casementioning
confidence: 99%
“…The use of conjugate priors is quite common in Bayesian statistics. Several authors (Geisser and Cornfield, 1963;Stone, 1964;Dickey, 1967;Logan and Gupta, 1993, to mention a few) have considered conjugate priors in the context of unknown covariance matrix. However, almost all have used an inverted Wishart density as the prior for the covariance matrix for a sole reason of mathematical tractability.…”
Section: Application To Bayesian Analysis Of the Multivariate Linear mentioning
confidence: 99%
“…In Bayesian analyses, (1) arises as: (a) the posterior distribution of the mean of a multivariate normal distribution [22,51]; (b) the marginal posterior distribution of the regression coefficient vector of the traditional multivariate regression model [54]; (c) the marginal prior distribution of the mean of a multinormal process [4]; (d) the marginal posterior distribution of the mean and the predictive distribution of a future observation of the multivariate normal structural model [20]; (e) an approximation to posterior distributions arising in location-scale regression models [52,53]; and (f) the prior distribution for set estimation of a multivariate normal mean [11]. Additional applications of (1) can be seen in the numerous books dealing with the Bayesian aspects of multivariate analysis.…”
Section: Definitionmentioning
confidence: 99%